Nawigując nurty zbrodni rzeki Jangcy. Analiza historycznej chińskiej gry detektywistycznej Murders on the Yangtze River - Kaniuk, Aleksandra Julia; Kidziak, Kacper Kajetan (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
In this case study of the historical Chinese detective game Murders on the Yangtze River, the authors explore the genre of detective games. The first part of this essay briefly introduces the game and the genre structures of detective games. The second part examines the game through the lens of detective games and their genre specific elements and structure. The last part presents an interpretation of how specific structural and design choices impact the reading of the game as a historical game. The essay ends with observations about the postcolonial potential of the game, suggesting direction for potential future studies.